2022
DOI: 10.3390/su14116811
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Unified Theory of Acceptance and Use of Technology for COVID-19 Contact Tracing Application by Malaysian Users

Abstract: The Malaysian government has mobilized its strength to confront the current COVID-19 pandemic and has sought to develop and implement a digital contact tracking application, making it an integral part of the exit strategy from the lockdown. These applications record which users have been near one another. When a user is confirmed with COVID-19, app users who have recently been near this person are notified. The effectiveness of these applications is determined by the users’ willingness to install and use them.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
2
3
0
Order By: Relevance
“…Additionally, social influence played a crucial role since it affected trust and intention with the highest effect compared to other predictors. This result was in line with previous studies in the context of trust (Beldad & Hegner, 2018;Oldeweme et al, 2021) and intention as an outcome (Aggelidis & Chatzoglou, 2009;Alshami et al, 2022;Huang et al, 2022;Oldeweme et al, 2021). Therefore, the surrounding encouragement influences the public's willingness to use the application.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Additionally, social influence played a crucial role since it affected trust and intention with the highest effect compared to other predictors. This result was in line with previous studies in the context of trust (Beldad & Hegner, 2018;Oldeweme et al, 2021) and intention as an outcome (Aggelidis & Chatzoglou, 2009;Alshami et al, 2022;Huang et al, 2022;Oldeweme et al, 2021). Therefore, the surrounding encouragement influences the public's willingness to use the application.…”
Section: Discussionsupporting
confidence: 91%
“…However, we did not explore the direct effect of privacy on intention. Since some studies found no significant effect of privacy on intention (Abuhammad et al, 2020;Alshami et al, 2022;Kwarteng et al, 2023), the effect might be mediated by attitude, as our study showed. On the other hand, perceived usefulness and perceived ease of use did not strongly impact attitude compared to trust after incorporating them with privacy concerns.…”
Section: Discussionsupporting
confidence: 38%
See 2 more Smart Citations
“…When the penetration rate of tracking applications in a country reaches 70%, the accurate tracking of populations can be achieved [ 21 ]. In Figure 8 , with different app application rates (AAR), the spread rate decreases with the increase of the app application rate.…”
Section: Experimental Simulationmentioning
confidence: 99%